Artificial Intelligence in Commerce and Business to Deal with COVID-19 Pandemic - et. al., Mohammed Arshad Khan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many countries imposed a complete lockdown in response to the increase in the number of COVID-19 patients. Hence, it results in the devastating global economic crisis across the globe. The pandemic vigorously affecting the services sectors, supply chain, and global trade business with visible repercussions in the increase in the unemployment rate in various indus-tries. The rapid pace of AI and technologies are helpful to reshape their business during this hard time. The application of AI is resulting in a business and commerce world which is in-novative and smart. The technological implication of AI simplifying our lives and business complexities. This escalates the popularity of Artificial Intelligence (AI) and its methods like the Heuristics method, Support vector machines(SVM), Markov Decision Process, Natural Language Processing (NLP), Fuzzy Logic, and Artificial Neural Network (ANN) to fathom the challenges arising due to the pandemic. Artificial Intelligence, Big Data, and Sensors are must in compliance with real-time data analysis, predictions for better decision making, in various sectors of the economy. The conglomerate, MSMEs, and start-up companies are em-phasizing more on the creation of digital enterprise leading by making their presence felt in various e-commerce platforms for the emergence of a new world. In this research paper, we also try to highlight some of the COVID-19 pandemic related issues that is basically affecting the commerce and business. This current